As dificuldades do ensino e aprendizagem em Matemática nas turmas de 1º ano do Ensino Médio da Escola Estadual João Vieira – Coari – Am - Coelho, Alex Bonfim (Brasil, 2025)
Mathematics is a fundamental subject in the school curriculum, as it develops cognitive, logical and analytical skills in students. Furthermore, mathematics is present in several areas of knowledge and is essential for understanding and solving everyday problems. However, many students face difficulties in learning this subject, which can harm their academic performance and their formation as citizens. In this context, the research in question became relevant, as it aims to investigate the difficulties in teaching and learning mathematics in 1st year high school classes at Escola Estadual João Vieira, in Coari, AM. Understanding the causes of these difficulties and proposing intervention strategies was fundamental to improving the teaching and learning of mathematics in this school and, consequently, promoting the academic success of students. The objectives of the project included identifying the possible causes that led students to be unable to perform mathematical operations, analyzing the effectiveness of the teaching methodology used by the teacher and checking with teachers the reasons that led to students' lack of understanding in mathematics classes. The research developed a mixed methodological approach, combining qualitative and quantitative techniques, and was based on case studies. Data was collected through questionnaires applied to students and teachers, allowing a deep understanding of the situation. Individual student factors, pedagogical practices and the school environment were considered. Data analysis made it possible to identify the main difficulties faced by teachers and students and propose provisions to overcome them. Furthermore, the research was able to provide support for teacher training and the development of more effective educational policies with regard to mathematics teaching.